2019
DOI: 10.1080/13102818.2019.1620633
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside protects against cerebral ischemia-reperfusion injury by alleviating oxidative stress, inflammation and apoptosis in rats

Abstract: This study investigated the effects of hyperoside pre-treatment on the oxidative stress, inflammatory response and apoptosis in rats with cerebral ischemia-reperfusion (I/R) injury. SD rats were randomly divided into sham, I/R, hyperoside (I/R þ Hyp) and nimodipine (I/R þ Nim) groups. The rats in the hyperoside group and the nimodipine group were intra-gastrically given hyperoside (50 mg/kg/day) and nimodipine (15 mg/kg/day), respectively, 15 days before operation. A rat cerebral ischemia model was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…However, as mentioned above, the presence of hesperidin and hyperoside in this plant was brought to the literature for the first time with this study. There are some literature data on the contribution of these compounds to antioxidant activity with some other plants or with these compounds themselves (Ku et al, 2014;Hao et al, 2016;Yatao et al, 2018;Gao et al, 2019;He et al, 2019;Kim et al, 2019;Musa et al, 2019;Aggarwal et al, 2020;Huang et al, 2020). These findings support the correlation coefficient data obtained from the present study.…”
Section: Discussionsupporting
confidence: 90%
“…However, as mentioned above, the presence of hesperidin and hyperoside in this plant was brought to the literature for the first time with this study. There are some literature data on the contribution of these compounds to antioxidant activity with some other plants or with these compounds themselves (Ku et al, 2014;Hao et al, 2016;Yatao et al, 2018;Gao et al, 2019;He et al, 2019;Kim et al, 2019;Musa et al, 2019;Aggarwal et al, 2020;Huang et al, 2020). These findings support the correlation coefficient data obtained from the present study.…”
Section: Discussionsupporting
confidence: 90%
“…And the reperfusion injury caused by cerebral I/R, including inflammation, apoptosis and so on, plays a key role in the process of I/R injury. 34 MicroRNA (miRNA) is involved in almost all known biological regulatory processes, such as cell differentiation, apoptosis, etc., and its effect is very potent. 35,36 It can be highly expressed as a biological marker in the human circulating blood system.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that phenylpropanoids and shikimate pathway enzymes reduce their activity under drought stress, as has been demonstrated in other plants (Mewis et al, 2012;Sanchez-Rodriguez et al, 2011). Previous studies (He et al, 2019;Liu et al, 2019;Qian et al, 2019) have shown that these compounds have antiinfective, immunomodulatory, and other pharmacological effects. Our results show that Eleuthero leaves have good medicinal value.…”
Section: )mentioning
confidence: 89%